1999
DOI: 10.1002/(sici)1521-3773(19990115)38:1/2<159::aid-anie159>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Hydrocarbons by a New Free Radical Based Condensation Reaction

Abstract: The Br. radical is the chain carrier of a new highly selective allylation of hydrocarbons (and other substrates): It abstracts a hydrogen atom from R−H to yield R.. Addition of R. to substituted allyl bromide (to form a β‐bromo radical) followed by β‐cleavage regenerates Br. and provides the product. Reaction yields and kinetic chain lengths for this reaction are highest when the allyl bromide contains a radical‐stabilizing substituent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Heating the DCM solution of 1u and C 4 F 9 I at 60°C in the dark, no desired 1,3-adduct 3uc was detected (see Supporting Information Scheme S2). In addition, we did not find any new signals in 19 F NMR by mixing 1u and C 4 F 9 I in CDCl 3 (see Supporting Information Figure S3). These results indicated that both photon absorbing and thermally sensitive EDA complexes cannot be formed between vinyldiazoacetates and R f I.…”
Section: Mechanistic Studiesmentioning
confidence: 79%
See 1 more Smart Citation
“…Heating the DCM solution of 1u and C 4 F 9 I at 60°C in the dark, no desired 1,3-adduct 3uc was detected (see Supporting Information Scheme S2). In addition, we did not find any new signals in 19 F NMR by mixing 1u and C 4 F 9 I in CDCl 3 (see Supporting Information Figure S3). These results indicated that both photon absorbing and thermally sensitive EDA complexes cannot be formed between vinyldiazoacetates and R f I.…”
Section: Mechanistic Studiesmentioning
confidence: 79%
“…Radical ring-opening of cyclopropanes would be an obvious method, but only reactive Br-radical is effective for σ-bond cleavage. [19][20][21] To make the process energetically feasible, ATRA reactions of activated alkyl halides with highly strained [1.1.1]propellanes have been developed (Scheme 1b-1). [22][23][24][25][26] Recently, the Studer group 27,28 disclosed an elegant radical 1,3-trifluoromethylation/alkynylation of allylboronic esters via 1,2-boron migration (Scheme 1b-2).…”
Section: Introductionmentioning
confidence: 99%
“…Alkyl radicals reacted with the bromide derivative via an addition−elimination reaction with generation of a bromine atom that added to the peroxyacetal carbon−carbon double bond. This is analogous to Tanko's mechanism for allylation with allyl bromide.…”
Section: Resultsmentioning
confidence: 52%
“…In stark contrast, bromine reagents have not been utilized in PRC reactions, but bromine radical (Br•) is well known as a moderately electrophilic HAT agent, which can abstract hydrogen atoms from C-H bonds to form nucleophilic carbon radicals. 11,[33][34][35][36][37] In this context, Ryu et al have developed various attractive bromine-radical mediated transformations. [35][36][37] Very recently, the Miyake group described an excellent study of bromine radical catalysis promoted by energy transferring photosensitization.…”
Section: Introductionmentioning
confidence: 99%